Development of 3D epidermal models: towards the development of a skin model for studies of the autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS) - Teixeira, Maria Beatriz Costa (2021)
Tese de mestrado, Biologia Molecular e Genética, Universidade de Lisboa, Faculdade de Ciências, 2021